Novel approach for the prediction of cell densities and viability in standardized translucent cell culture biochips with near infrared spectroscopy. Issue 5 (12th January 2017) - Gröger, Marko; Lange, Matthias; Rennert, Knut; Kaschowitz, Tobias; Plettenberg, Holger; Hoffmann, Martin; Mosig, Alexander S.
Abstract : Near infrared spectroscopy is a rapid and nondestructive method for compositional analysis of biological material. The technology is widely used within bioreactors and possesses potential as a standardized method for quality control in miniaturized microfluidic cell culture systems. Here, we established a method for quantification of cell density and viability of adherent HepaRG cells cultured in a translucent, miniaturized cell culture biochip. The newly developed statistical models for interpretation of near infrared spectroscopy from biochips are the basis for a novel method of fast, continuous, and contact‐free analysis of cell viability and real‐time monitoring of cell growth. The technique thus paves the way for a robust and reliable high‐throughput analysis of biochip‐embedded cell cultures.